Molecular Imaging with Reporter Genes / [electronic resource] - Gambhir, Sanjiv Sam; Yaghoubi, Shahriar S. (Cambridge : Cambridge University Press, 2010)
Reporter genes have been used for several decades to study regulation of gene expression in vivo. However, it was little more than a decade ago that a new class of reporter genes was developed for imaging molecular events within living subjects. By following the interactions of protein molecules, researchers can resolve the complex chemical pathways that living cells utilise. This book focuses on this group of imaging reporter genes, starting with detailed descriptions of all reporter genes from different imaging modalities, including optical, MRI, and radionuclide-based imaging. Key scientists in the field explain how to enhance reporter gene imaging utility through instrumentation and the various applications of this technology. This is the first comprehensive book on all aspects of reporter gene imaging, detailing what is known in the field and future goals for research. Investigators in biomedical sciences, physicians, and the biotechnology and pharmaceutical industries will benefit from topics covered.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Reporter genes; Molecular probes; Diagnostic imaging